Educação Ambiental na Prática de Professoras do Ensino Fundamental I (Humaitá,Amazonas, Brasil) - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
This research had as object of study to investigate what was developed about the objects of knowledge of EA in curriculum documents (class diaries) and its relationship with the educational practice, developed in the Postgraduate Program in Teaching of Sciences and Humanities, from the Institute of Education, Agriculture and Environment, from Federal University of Amazonas. In this work we sought to investigate the following problem: How have been developing teaching practices for the effectiveness of interdisciplinary teaching of Environmental Education in Elementary School I? This problem leads us to reflect on the teaching profession, where the teacher is in the expectation about their practice within the school community, where the teacher is charged, questioned, and most of the time they do not have time to devote to the real needs of teaching and learning of their students. The objective of this research was to analyze the teaching practices for the development of Environmental Education in Elementary School I, in a School at the town of Humaitá-Amazonas. This research had a qualitative nature and the data was analyzed through Content Analysis, proposed by Bardin (2016). Thus, we sought a theoretical reference on the new perspectives of Environmental Education for a critical and reflective education; the survey of global discussions around the environmental theme and its Brazilian educational legislation; the study of teacher training to work in Elementary School I; the teaching practice within the context of EA. In this perspective, the perception, professional training and teaching practice of teachers were rescued, in regarding to environmental issues. To this end, five (05) teachers working in Elementary School I, from the 1st to the 5th year of the municipal network of Humaitá in the State of Amazonas, participated in this research. In this process, it was verified through the analysis of the class diaries and the answers to the semi-structured questionnaire that educators emphasize a naturalistic view of the environment, in other words, it is centered on the relationship with nature, perceiving the environment in a natural way, the place from which resources are extracted and needs to be preserved. The results also showed how the teaching practices of teachers are related to their perceptions about EA, where they point to discontinuity and fragmented activities. We highlighted, therefore, the importance of this research, which proposed to address a guiding by critical and reflective character, considering the social, historical and political aspects, which the insertion of the environmental theme is involved, in addition to highlighting the commitment to reflect on our conceptions, actions and teaching practice in the classroom. Keywords: Environmental Education, Teaching Practice, Teacher, Elementary School I.
Keywords: Consciência ambiental; Professores - Formação; Prática educativa; Ensino e aprendizagem; Conservação da natureza; CIÊNCIAS HUMANAS; Educação Ambiental; Prática Docente; Professora; Ensino Fundamental I; Cidadania Ambiental